Upaya Public Relations Gen FM dalam Membangun Hubungan dengan Stakeholder Melalui Instagram @Gen987fm - Marshella Anisa Gilera; Laksmi Rachmaria (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the Public Relations (PR) strategy of Gen FM in building and maintaining relationships with stakeholders through its official Instagram account, @gen987fm. The background of this research lies in the paradigm shift of PR communication patterns from conventional to digital platforms, alongside the growing importance of establishing long-term, strategic relationships in the era of media convergence. The study adopts Ledingham and Bruning’s Relationship Management (RM) theory as its analytical framework, which consists of five key dimensions: trust, commitment, openness, relationship satisfaction, and mutual interest. Employing a descriptive qualitative approach, data were collected through in-depth interviews with Gen FM’s PR team, the Head of Digital Content, selected audience members, and business partners. These interviews were further supported by observation and documentation of content published on Instagram. The findings reveal that Gen FM effectively applies the five dimensions of relationship management theory in its PR practices through digital media. Trust is fostered by presenting credible and relevant content; commitment is demonstrated by maintaining consistent interactions with audiences; openness is shown by accommodating feedback and criticism; satisfaction is achieved through personal and engaging approaches; and mutual interest is realized through promotional collaborations that benefit both the radio station and its partners. Nevertheless, stakeholders also expressed expectations for Gen FM to further enhance its Instagram presence by being more active, responsive, and innovative in order to strengthen engagement and adapt to the dynamic needs of digital audiences. In conclusion, this study emphasizes that Instagram functions as an effective medium for Gen FM to implement strategic and adaptive PR relationship management. The platform not only facilitates two-way communication but also strengthens brand positioning by fostering sustainable stakeholder relationships in a rapidly evolving digital landscape.